PENGARUH SELF HYPNOSIS TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III DALAM PERSIAPAN MENGHADAPI PERSALINAN DI UPTD. PUSKESMAS ABIANSEMAL II - Rusmini, Desak Made; Mastiningsih, Putu; Widiastini, Luh Putu (Universitas Prima Indonesia, 2024)
The third trimester of pregnancy is often referred to as a period of anxious anticipation. A primary effort to reduce the level of anxiety and fear in pregnant women is through the provision of Self Hypnosis. Known not only as a powerful anti-anxiety agent, Self Hypnosis also induces a high level of relaxation. The aim of this study was to determine the Effect of Self Hypnosis on the Anxiety Level of Third Trimester Pregnant Women in Preparation for Childbirth at UPTD. Puskesmas Abiansemal II. This study employed a quasi-experimental design with a nonequivalent control group design. The sample selection was carried out using purposive Sampling technique. The sample consisted of all third trimester pregnant women, totaling 56 individuals. The intervention was initially administered by the researcher along with an instructor on the first day of the study. Subsequently, it was performed by the pregnant women themselves before getting up in the morning and before going to bed at night, with a duration of 5 minutes each day for 5 days. The study was conducted from November to December 2023. Data were analyzed using the Mann Whitney Test. The results of the study, utilizing the Mann Whitney test, revealed a p-value of 0.014 (p<0.05), indicating that the null hypothesis was rejected. Therefore, it can be concluded that there is an effect of Self Hypnosis on the Anxiety Level of Third Trimester Pregnant Women at UPTD. Puskesmas Abiansemal II. In conclusion, it is hoped that third trimester pregnant women can overcome anxiety in preparation for childbirth.